Advanced medical micro-robotics for early diagnosis and therapeutic interventions - Dandan Zhang; Dandan Zhang; Thomas E. Gorochowski; Thomas E. Gorochowski; Lucia Marucci; Lucia Marucci; Lucia Marucci; Hyun-Taek Lee; Bruno Gil; Bing Li; Bing Li; Bing Li; et al. (Frontiers in Robotics and AI, 2023)
Recent technological advances in micro-robotics have demonstrated their immense potential for biomedical applications. Emerging micro-robots have versatile sensing systems, flexible locomotion and dexterous manipulation capabilities that can significantly contribute to the healthcare system. Despite the appreciated and tangible benefits of medical micro-robotics, many challenges still remain. Here, we review the major challenges, current trends and significant achievements for developing versatile and intelligent micro-robotics with a focus on applications in early diagnosis and therapeutic interventions. We also consider some recent emerging micro-robotic technologies that employ synthetic biology to support a new generation of living micro-robots. We expect to inspire future development of micro-robots toward clinical translation by identifying the roadblocks that need to be overcome.